Rev1 is essential in generating G to C transversions downstream of the Ung2 pathway but not the Msh2+Ung2 hybrid pathway. Issue 10 (5th August 2013) - Krijger, Peter HL; Tsaalbi‐Shtylik, Anastasia; Wit, Niek; van den Berk, Paul Cornelius Maria; de Wind, Niels; Jacobs, Heinz
<x xml:space="preserve">Abstract</x> Somatic hypermutation (SHM) and class switch recombination (CSR) of immunoglobulin (Ig) genes are initiated by the enzymatic deamination of cytosine (C) to uracil (U). Uracil‐DNA‐glycosylase (Ung2) converts uracils into apyrimidinic (AP) sites, which is essential for the generation of transversions (TVs) at G/C basepairs during SHM and for efficient DNA break formation during CSR. Besides Ung2, the mismatch repair protein Msh2 and the translesion synthesis (TLS) DNA polymerase (Pol) Rev1 are implicated in SHM and CSR. To further unravel the role of Rev1, we studied WT, Rev1‐deficient, Msh2‐deficient, and Rev1, Msh2 double‐deficient B cells. Loss of Rev1 only slightly reduced CSR. During SHM G/C to C/G TVs are generated in both Ung2‐ and Ung+Msh2‐dependent fashions. We found that Rev1 is essential for the Msh2‐independent generation of these TVs downstream of Ung2‐induced AP sites. In the Ung+Msh2 hybrid pathway, Rev1 is not essential and can be substituted by an alternative TLS Pol, especially when Rev1 is lacking.